The Indonesian Survivors’ Perspective about Recovery from Schizophrenia: An Exploratory Study - Suryani Suryani; Nurul Hidayah; Titin Sutini; Lilibeth Al-Kofahy (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Recovering from schizophrenia is a unique process and is inﬂuenced by the cultural background of survivors. Purpose: The purpose of this study is to describe the important aspects of the recovery process of Indonesian people living with schizophrenia. Methods: This study used qualitative exploratory descriptive and data were collected through focus group discussion with seven participants at a Residents ofce on July 2018. Data were analysed using the theory of Braun and Clarke to identify key themes. Results: Five themes arose from this study including becoming an agent of recovery, accepting yourself as you are, keeping a smile in all situations, seeking God’s help as a way to get well, and ignoring by the government. Conclusion: It was concluded that, in the process of recovery, survivors became agents of recovery, so patient-centred care becomes very important in providing nursing care to the survivors. The result of this research can be considered for community nurses in caring for schizophrenia survivors.